Hymenolepis diminuta Infection in a School Going Child: First Case Report from Uttarakhand - Gupta, Pratima (J Clin Diagn Res, 2016)
Hymenolepis diminuta (H.diminuta) is prevalent worldwide, and a few hundred human cases have been reported till date. It is primarily a rodent parasite and humans (usually children) can act as accidental hosts. Infections are usually asymptomatic but abdominal pain, irritability, pruritis, mild diarrhoea and eosinophilia are among the existing symptoms in a few of the reported cases. Here, we report a case of an 11-year-old female child from Bijnor, who presented to us with complaints of abdominal pain, fatigue and irregular episodes of fever. Routine stool examination showed characteristic eggs of H.diminuta. Patient was given a single oral dose of praziquantel (25 mg/kg) and she improved. This case is presented to emphasize that till date there are very few reports on H.diminuta and there is limited data regarding its treatment protocols (dose and duration). Furthermore, albendazole which is commonly used drug for deworming helminthic infections is less effective in these infections.